Sports research with analytical solution using SPSS - Verma, J. P. (Wiley-Blackwell, 2015)
Introduces the applications of repeated measures design processes with the popular IBM(r) SPSS(r) software. Repeated Measures Design for Empirical Researchers presents comprehensive coverage of the formation of research questions and the analysis of repeated measures using IBM SPSS and also includes the solutions necessary for understanding situations where the designs can be used. In addition to explaining the computation involved in each design, the book presents a unique discussion on how to conceptualize research problems as well as identify appropriate repeated measures designs for research purposes.